2010
DOI: 10.1093/ndt/gfq212
|View full text |Cite
|
Sign up to set email alerts
|

Broadening Options for Long-term Dialysis in the Elderly (BOLDE): differences in quality of life on peritoneal dialysis compared to haemodialysis for older patients

Abstract: Background. Health-related quality of life (QOL) is an important outcome for older people who are often on dialysis for life. Little is, however, known about differences in QOL on haemodialysis (HD) and peritoneal dialysis (PD) in older age groups. Randomising patients to either modality to assess outcomes is not feasible.Methods. In this cross-sectional, multi-centred study we conducted QOL assessments (Short Form-12 Mental and Physical Component Summary scales, Hospital Anxiety and Depression Scale and Illne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
125
2
11

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(141 citation statements)
references
References 39 publications
3
125
2
11
Order By: Relevance
“…There was no difference in 1-year mortality in 125 patients older than age 70 years in the North Thames Dialysis Study (57). The BOLDE (Broadening Options for Long-term Dialysis in the Elderly) study found similar quality of life for PD versus HD in prevalent elderly (.65 years) patients (49). In 3512 incident French dialysis patients older than 75 years (Renal Epidemiology and Information Network registry), the 2-year PD survival rate was 64%, similar to that seen with HD (58).…”
Section: Choice Of Rrt Hd Versus Peritoneal Dialysismentioning
confidence: 97%
See 2 more Smart Citations
“…There was no difference in 1-year mortality in 125 patients older than age 70 years in the North Thames Dialysis Study (57). The BOLDE (Broadening Options for Long-term Dialysis in the Elderly) study found similar quality of life for PD versus HD in prevalent elderly (.65 years) patients (49). In 3512 incident French dialysis patients older than 75 years (Renal Epidemiology and Information Network registry), the 2-year PD survival rate was 64%, similar to that seen with HD (58).…”
Section: Choice Of Rrt Hd Versus Peritoneal Dialysismentioning
confidence: 97%
“…Although HD may be an effective and attractive option (supervised, not done daily), elderly patients are generally more sensitive to fluid shifts because of increased cardiovascular comorbidity and may not tolerate ultrafiltration (49,50). In addition, problems with transportation and vascular access can limit success.…”
Section: Choice Of Rrt Hd Versus Peritoneal Dialysismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, living-donor kidney transplantation can be a viable option, even for elderly patients, if they meet set criteria (30). Peritoneal dialysis is an acceptable alternative to in-center hemodialysis in terms of survival (31), satisfaction (32), and improved quality of life for many elderly patients (33). Initiation of hemodialysis can sometimes be delayed by a very-low-protein diet, and an Italian study achieved an average delay for hemodialysis commencement of 10.9 months (34).…”
Section: Preserving Patient Autonomymentioning
confidence: 99%
“…For elderly patients, peritoneal dialysis (PD) offers advantages of particular interest, such avoidance of the need to travel to the dialysis center three times each week (9), less hemodynamic instability (9), lower risk of central venous catheter-associated bacteremia (10), and better control of blood pressure (10,11). Beyond the cognitive, social, physical, and psychological limitations (12,13) of such patients, many associated comorbidities may also be present, complicating implementation of the PD technique, because many elderly patients live by themselves and have no family support (14).…”
mentioning
confidence: 99%